Integration of the ASR Toolkit Kaldi Into a Domoticz Home Automation System - Aboulhir, Mohamed; Khoulji, Samira; Jourani, Reda; Kerkeb, ML (Transactions on Engineering and Computing Sciences, 2017)
This paper presents the design and the implementation of an interface between Kaldi, automatic speech recognition toolkit, and a home automation system. This interface is based on Open Platform communication (OPC) protocol. The developed architecture allows the injection of vocal data into a home automation system. Developed in C++, The Kaldi behaves as aclient of the OPC server.